Co-occurrence Strength and Transitivity Effects on Spanish Clitic Case Variation With Reverse-Psychological Predicates - Guajardo, Gustavo (Frontiers in Psychology, 2021)
Although the most frequent psychological predicates in Spanish require the third-person clitic experiencer to appear in dative case, there is a well-known subclass of predicates for which the case of the clitic alternates between accusative and dative. This alternation has been previously accounted for by certain grammatical properties of the clause containing the clitic as well as elements of transitivity. However, since most studies on the subject have only looked at a subset of the elements comprising transitivity, it remains to be demonstrated whether the alternation in clitic case can reliably be reduced to a difference in transitivity. In this paper, I study the extent to which transitivity is the main predictor of clitic case alternation with reverse psychological predicates by comparing its effect with another potential predictor, namely the bidirectional association strength between the verb and the clitic. The results show that higher levels of association between the clitic and the verb favour the dative clitic, suggesting a higher degree of lexicalization of the dative clitic-verb pair. Furthermore, although it is found that higher levels of transitivity favour the accusative clitic, the effect is rather small compared to the rest of the predictors. All in all, the results support previous findings in the literature, but they also bring to the fore the importance of frequency of co-occurrence on Spanish clitic case alternation in particular, and language variation more generally.